Dynamic modeling of the birefringence effects induced in semiconductor optical amplifier for all-optical telecommunication systems - A. Elyamani; A. Zatni; A. Moumen; H. Bousseta (International Journal of Reconfigurable and Embedded Systems (IJRES), 2020)
The semiconductor optical ampliﬁers (SOA) are all-optical multifunctional devices. The improvement of their performance will, therefore, be of great importance for modern optical telecommunication systems. We propose in this article to develop a dynamic model that enables us to simulate the dynamic behavior of SOA's birefringence effects. The determination of a numerical model is a multidisciplinary activity that needs engineering skills, optimization and physics. This numerical model enables to describe the propagation of a picosecond optical pulse passing through the SOA and takes into account its polarization and the phenomenon of energy coupling between the eigenmodes of SOA (TE mode and TM mode). In this paper, we will, first of all describe the numerical algorithm of our model, and then we will propose to make a dynamic characterization of the effect of the nonlinear polarization rotation in the SOA, which will allow us to study the all-optical logic gates as well as all the other digital components based on the nonlinear effect of birefringence in SOA.